Argentine wild Helianthus annuus L. as a genetic resource for Sunflower Chlorotic Mottle Virus (SuCMoV) resistance - Cantamutto, Miguel Ángel (2010)
In the last sixty years, wild sunflower (Helianthus annuus L.) naturalized in the central region of Argentina. The invasive process was accomplished by an increase in genetic variability due to the gene flow with domestic sunflower and the prairie sunflower (H. petiolaris L.). It is possible that the tolerance to abiotic stress and increased disease resistance contributed to the effective colonization of new environments. Sunflower chlorotic mottle virus (SuCMoV), a member of the potyvirus family, is considered an emergent hazard for the sunflower crop under agricultural conditions prevailing in Argentina. Two populations of wild sunflowers collected in La Pampa and Buenos Aires exhibiting increased tolerance (61% and 35%, respectively) were identified after artificial inoculation with SuCMoV. Tolerant individuals from these populations were crossed among themselves and with HA89, A09 and A10 male sterile inbred lines (IL). After two generations of recurrent selection for virus resistance, the same inbred lines were pollinated by individuals classified as susceptible (S) or tolerant (T). The progeny of crosses IL x S showed 98% of susceptibility while IL x T have only 58%. In crosses involving T specimens, 22% of the plants showed attenuated mottled symptoms, considered as a virus resistance mechanism. The selection process has been delayed due to the self incompatibility mechanism characteristic of the wild genotypes. A low proportion of escapes included as immune plants also hindered the selection process. It is expected that these limitations will be overcome by means of crosses with self compatible maintainer inbred lines (B) and adjustments in the inoculation technique.